Histone depletion prevents telomere fusions in pre-senescent cells. - Marta Barrientos-Moreno; Marina Murillo-Pineda; Ana M Muñoz-Cabello; Félix Prado (PLoS Genetics)
Upon telomerase inactivation, telomeres gradually shorten with each cell division until cells enter replicative senescence. In Saccharomyces cerevisiae, the kinases Mec1/ATR and Tel1/ATM protect the genome during pre-senescence by preventing telomere-telomere fusions (T-TFs) and the subsequent genetic instability associated with fusion-bridge-breakage cycles. Here we report that T-TFs in mec1Δ tel1Δ cells can be suppressed by reducing the pool of available histones. This protection associates neither with changes in bulk telomere length nor with major changes in the structure of subtelomeric chromatin. We show that the absence of Mec1 and Tel1 strongly augments double-strand break (DSB) repair by non-homologous end joining (NHEJ), which might contribute to the high frequency of T-TFs in mec1Δ tel1Δ cells. However, histone depletion does not prevent telomere fusions by inhibiting NHEJ, which is actually increased in histone-depleted cells. Rather, histone depletion protects telomeres from fusions by homologous recombination (HR), even though HR is proficient in maintaining the proliferative state of pre-senescent mec1Δ tel1Δ cells. Therefore, HR during pre-senescence not only helps stalled replication forks but also prevents T-TFs by a mechanism that, in contrast to the previous one, is promoted by a reduction in the histone pool and can occur in the absence of Rad51. Our results further suggest that the Mec1-dependent depletion of histones that occurs during pre-senescence in cells without telomerase (tlc1Δ) prevents T-TFs by favoring the processing of unprotected telomeres by Rad51-independent HR.